Dampak Harmonisasi Regulasi Farmasi terhadap Akses Obat dan Keamanan Pasien - Aminudin; Azzahra, Naila; Putri, Tiara Ananda; Aprianto, Yakobus (Pharmaceutical Journal, 2025)
This study is a literature review that aims to comprehensively examine health and drug regulation from three perspectives: the implementation of Real-World Evidence (RWE), the application of Good Regulatory Practices for Medicines (CROB), and a comparison of health regulations across countries. Using a literature review method, the findings indicate that Indonesia faces significant challenges in integrating RWE into its drug approval system, particularly due to limited data infrastructure, regulatory gaps, and data ethics issues. On the other hand, the CROB guidelines issued by the National Agency of Drug and Food Control (BPOM) represent a crucial effort to build a regulatory system that is transparent, accountable, and evidence-based. Furthermore, cross-country comparisons affirm that strict regulations positively impact the quality of healthcare services, enhancing patient safety and the competence of medical personnel. This study concludes that adaptive, integrated, and consistent regulation is essential to ensure the quality of medicines and healthcare services, and that harmonizing policies across sectors and countries is necessary to address global health challenges.